2023
DOI: 10.1212/nxi.0000000000200049
|View full text |Cite
|
Sign up to set email alerts
|

Kappa Free Light Chain Biomarkers Are Efficient for the Diagnosis of Multiple Sclerosis

Abstract: Background and ObjectivesKappa free light chains (KFLC) seem to efficiently diagnose MS. However, extensive cohort studies are lacking to establish consensus cut-offs, notably to rule out non-MS autoimmune CNS disorders. Our objectives were to (1) determine diagnostic performances of CSF KFLC, KFLC index, and KFLC intrathecal fraction (IF) threshold values that allow us to separate MS from different CNS disorder control populations and compare them with oligoclonal bands' (OCB) performances and (2) to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 45 publications
4
28
0
Order By: Relevance
“…9 Another very recent large multicenter study including more than 1600 patients also reported that κ-FLC index and IF κ-FLC performed slightly better than absolute CSF κ-FLC concentration. 62 Further studies are required to compare the different κ-FLC measures in patients with varying degree of intrathecal B cell activity and varying blood–CSF-barrier function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Another very recent large multicenter study including more than 1600 patients also reported that κ-FLC index and IF κ-FLC performed slightly better than absolute CSF κ-FLC concentration. 62 Further studies are required to compare the different κ-FLC measures in patients with varying degree of intrathecal B cell activity and varying blood–CSF-barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find a statistically significant impact of assay and platform on κ-FLC index, in line with a recent large multicentre study that also did not observe any impact of the platform on κ-FLC index. 62 Using the ratio of the CSF and serum κ-FLC concentration (for calculating the index) might be less prone to laboratory variations. The potentially different susceptibility of κ-FLC index and absolute CSF κ-FLC concentrations to laboratory variation should be further addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The index is obtained by linear modeling to calculate the concentration of KFLC in serum and CSF. The formula of KFLC index is: FLC index = Q FLC/ Q alb with Q FLC = CSF FLC/serum FLC and Q alb = CSF albumin/serum albumin ( 47 ). Similar to CSF KFLC, KFLC index is better than OCB in the diagnosis of MS and differentiation of MS and other inflammatory CNS disorders ( 44 , 47 , 48 ), so KFLC index may replace OCB as a first-line biomarker of MS in clinical practice.…”
Section: Kflc Indexmentioning
confidence: 99%
“…The formula of KFLC index is: FLC index = Q FLC/ Q alb with Q FLC = CSF FLC/serum FLC and Q alb = CSF albumin/serum albumin ( 47 ). Similar to CSF KFLC, KFLC index is better than OCB in the diagnosis of MS and differentiation of MS and other inflammatory CNS disorders ( 44 , 47 , 48 ), so KFLC index may replace OCB as a first-line biomarker of MS in clinical practice. The early initiation of DMDs in MS is important to slow down progression in disability and cognitive impairment.…”
Section: Kflc Indexmentioning
confidence: 99%
“…A very recent large multicenter study including more than 1600 patients also reported that κ-FLC index and IF κ-FLC performed slightly better than absolute CSF κ-FLC concentration. 63 Further studies are required to compare the different κ-FLC measures in patients with varying degrees of intrathecal B-cell activity, varying blood-CSF-barrier function and varying serum κ-FLC concentrations, as the impact of grossly elevated serum FLC levels or elevated Q alb has not been sufficiently investigated. This might be of interest also in terms of differential diagnosis, as, for example, NMOSD sometimes shows considerable blood-CSF-barrier dysfunction, 13 which might lead to higher diffusion of κ-FLC from the blood into CSF and possibly to false-positive results if only absolute CSF κ-FLC concentrations are measured.…”
Section: Diagnostic Accuracy Of Intrathecal κ-Flc Synthesis In Patien...mentioning
confidence: 99%